2000
DOI: 10.1097/00005373-200001000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Improvements in Prehospital Trauma Care in a Latin American City

Abstract: Increase in sites of dispatch and increased training in the form of the PHTLS course improved the process of pre-hospital care in this Latin American city and resulted in a decrease in prehospital deaths. These improvements were low cost and should be considered for use in other less developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 10 publications
0
98
0
8
Order By: Relevance
“…Studies from other low-and middle-income countries have shown that prehospital trauma training programs can reduce mortality [6,23,24]. The same was shown for hospital-based care from Trinidad where regular implementation of an ATLS-course led to reduced mortality in severely injured patients [25].…”
Section: Staffing and Trainingmentioning
confidence: 82%
“…Studies from other low-and middle-income countries have shown that prehospital trauma training programs can reduce mortality [6,23,24]. The same was shown for hospital-based care from Trinidad where regular implementation of an ATLS-course led to reduced mortality in severely injured patients [25].…”
Section: Staffing and Trainingmentioning
confidence: 82%
“…Two reports specifically addressed the impact of establishing or reorganizing dispatch systems to improve access to care. In Monterrey, Mexico, an increase from 2 to 4 ambulance dispatch stations decreased mean response time by 40%; coupled with training, these prehospital care improvements cost only US$77,600 per year (16% of the annual system budget) (13). A new dispatch algorithm implemented in Tehran, Iran (Islamic Republic of ), improved utilization of existing resources and resulted in a 16% decrease in unnecessary trauma responses (7).…”
Section: Records After Abstract Screening (N = 163)mentioning
confidence: 99%
“…Reynolds et al Process (3,5,6,9,12,13,14,15,20,21,46,50,53,54,57,64,67,68,69,71,86,93,103) 23 (32) Clinical or population health outcome (3,4,12,14,15,16,17,18,19,22,23,24,28,29,35,36,41,42,43,45,48,49,53,54,57,59,60,61,64,…”
mentioning
confidence: 99%
“…33 In middle-income settings where emergency medical services do exist, relatively low-cost interventions could have a substantial impact on improving prehospital trauma care such as a wider geographical distribution of ambulance dispatch and further training for ambulance staff which have been shown to be highly effective in Latin America. 35 …”
Section: First Aid Training For Traumamentioning
confidence: 99%